Estimation of leachate from a pilot scale lysimeter - Manandhar, Dinesh Raj; Hogland, William; Krishnamurthy, V; Khanal, Sanjay Nath (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The most important component of solid waste management is long-term safe and reliable disposal of solid waste in sanitary landfills. Leachate formed in landfills needs proper management. The biodegradable portion of waste is largely responsible for the production of leachate and landfill gas. This paper presents the outcome of the research on the water management of landfill in Nepal using a designed and built pilot scale field lysimeter model. The leachate production from the lysimeter as an effect of climatological factors is assessed. The Hydrologic Evaluation of Landfill Performance (HELP) model is used to compute estimates of water balances. Simulation of the model indicates that the evapotranspiration (ET) is nearly constant and do not follow the precipitation and percolation trend. Also the evapotranspiration component in this case, is not high. This may be due to the small surface area of lysimeter and larger portion of the leachate percolated before evaporation could take place. The model has been calibrated for the local situation with the limited observed data of leachate generation from the lysimeter. However the trend of leachate generation on HELP simulation and Actual Data seem to be similar during month of October to December season, but during June to September, the trend shows higher actual percolation rate compared to the model output. This may be due to the higher value of permeability of barrier soil (in the range of 10-5 cm/s), which should be generally in the range of 10-7 cm/s or lower. The rainy season during June to September may be another reason, when soil is wet most of the time. The annual data shows that percolation is about 81-84% of precipitation amount, whereas evapotranspiration is about 15-19%. The application of the model may be a valuable tool to determine strengths and weaknesses of designing and operating of landfills in developing countries like Nepal. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 93-100 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7331